An Observational Study of Bullying as a Contributing Factor in Youth Suicide in Toronto. (December 2014) - Sinyor, Mark; Schaffer, Ayal; Cheung, Amy H
Objective: Bullying has been identified as a potential contributing factor in youth suicide. This issue has been highlighted in recent widely publicized media reports, worldwide, in which deceased youth were bullied. We report on an observational study conducted to determine the frequency of bullying as a contributing factor to youth suicide. Method: Coroner records were reviewed for all suicide deaths in youth aged between 10 and 19 in the city of Toronto from 1998 to 2011. Data abstracted were recent stressors (including bullying), clinical variables, such as the presence of mental illness, demographics, and methods of suicide. Results: Ninety-four youth suicides were included in the study. The mean age was 16.8 years, and 70.2% were male. Bullying was present in 6 deaths (6.4%), and there were no deaths where online or cyberbullying was detected. Bullying was the only identified contributing factor in fewer than 5 deaths. The most common stressors identified were conflict with parents (21.3%), romantic partner problems (17.0%), academic problems (10.6%), and criminal and (or) legal problems (10.6%). Any stressor or mental and (or) physical illness was detected in 78.7% of cases. Depression was detected in 40.4% of cases. Conclusions: Our study highlights the need to view suicide in youth as arising from a complex interplay of various biological, psychological, and social factors of which bullying is only one. It challenges simple cause-and-effect models that may suggest that suicide arises from any one factor, such as bullying.